Interfacial engineering for high performance carbon-based perovskite solar cells - Brown, Megan; Li, Dawen (Frontiers in Energy Research, 2024)
Perovskite solar cells fabricated with carbon-based counter electrodes demonstrate decreased cost, enhanced simplicity and speed of production, and increased stability compared to those produced with standard metallic electrodes. This significant improvement of device stability, cost reduction, and production scalability indicates a promising direction for commercial development and availability of perovskite solar technology. The main limitation of carbon-based perovskite devices is the flawed contact between the carbon electrode and perovskite film which decreases device quality and performance, thereby necessitating treatment of the carbon/perovskite interface. This review provides an overview of the current state of carbon-based perovskite devices, discusses progress in carbon/perovskite interface modification methods, and suggests future directions for the research of carbon electrode/perovskite film interface manipulation.